A avaliação no ensino superior: concepções múltiplas de estudantes brasileiros - Daniel Abud Seabra Matos (2010)
The goals of this study were to (1) overview Brazilian university students conceptions of assessment; (2) adapt and validate the Students' Conceptions of Assessment (SCoA) - version VI - inventory (Brown, 2006) for the Brazilian context; (3) establish the underlying dimensions shaping Brazilian university students definitions of assessment; (4) analyze how conceptions of assessment predict students definitions of assessment;and (5) investigate differences between students at public and private universities. We used as theoretical framework the theory of self-regulated learning. Four studies were carried out using a mixture of quantitative (multidimensional scaling, exploratory and confirmatory factor analysis, analysis of variance, structural equation modeling) andqualitative (content analysis was used to investigate the open-ended questions in the survey) methods. Students enrolled in 18 undergraduate courses (N = 756, 216 males and 540 females, age M = 24.53 years, SD = 5.91) from two universities in the state of Minas Gerais participated in 2008 year (nonrandom sample): a public university (N = 297) and a private University (N = 459). The Brazilian SCoA responses fit well to theoriginal eight factors structure of the questionnaire (TLI = .95; gamma hat = .92, SRMR = .057). Students defined assessment in terms of their formality and who was in control of them, resulting in four types of assessment practices: informal student-controlled; informal teacher-controlled; formal student-controlled; and formal eacher-controlled. The students emphasized conventional, formal evaluation methods controlled by the teacher. Even supposedly student-controlled practices (i.e., self and peer-assessments)were perceived as teacher-controlled practices. As a whole, the university students conceived assessment most strongly as being about improvement, and second as about accountability. From the analysis of the open-ended questions attached to the SCoA, three analytical categories arose: a) perceptions about the functions or roles ofassessment; b) perceptions about assessment effects; and c) perceptions about education itself. The definitions of assessment were meaningfully predicted by student responses to key factors in the SCoA inventory. The SCoA factor of "Improvement" was only associated with formal practices and those controlled by the teacher. Formal practices,whether controlled by students or teachers, decreased as agreement with assessment as an enjoyable experience and something bad. In other words, we might hear students say something like: "If assessment is formal, I do not necessarily think it's an enjoyable